Glycine max in multiple macrophages - Qutaiba Al-Nuama (College of Education for Pure Sciences, 2005)
The present study aimed to establish cell suspension from stem callus of Glyc'me max. These suspensions were cultured by embedding them in agar, This technique was favorable for cell division, colonies formation and microcalli production. The results indicate that the best growth of cells was 174 x 106 cell / ml in the sixth day with viability between 47- 81 %,